How to build a billion dollar app : discover the secrets of the most successful entrepreneurs of our time - Berkowski, George (Piatkus, 2017)
A billion humans now have smartphones. We've downloaded more than 500,000 different apps more than 35 billion times. Apps are not only changing the way we communicate, shop, interact and travel, but they are becoming the dominant platform by which we manage many parts of our lives. Despite this, there are only a handful of mobile businesses that have cracked the code to making it billion-dollar big. George Berkowski is one of the masterminds behind one app on its way to breaking into this elite group - Hailo - the smartphone app which allows users to hail taxis from their mobile phones. In How to Build a Billion Dollar App, George draws on his experiences as Head of Product at Hailo, founder of internet dating startup WooMe (sold to Zoosk in 2011) and advisor to Fly Victor (the startup currently revolutionising - and disrupting - the private aviation industry) to show readers how to translate an idea for an app into a real world service, product and business. How to Build a Billion Dollar App provides practical advice on the nitty-gritty of building an app-based business - from the mechanics of user acquisition to securing the funding necessary for growth - interwoven with the inside story of Hailo and other billion dollar apps including Angry Birds, Whatsapp, Snapchat and Square. It will be essential reading for anybody with a great idea for an app-based business.